1995
DOI: 10.1007/bf01323238
|View full text |Cite
|
Sign up to set email alerts
|

A block in glycoprotein processing correlates with small plaque morphology and virion targetting to cell-cell junctions for an oral and an anal strain of herpes simplex virus type-1

Abstract: The characteristics of two clinical isolates of HSV-1 obtained from an oral (424) and an anal (490) lesion were compared with the highly passaged KOS strain. In contrast to KOS, the clinical isolates produced small plaques, were more cell-associated and the predominant viral glycoprotein species for gC and gD in infected cell lysates was the precursor, high mannose glycoform. Total virus production in Vero cells was equivalent for the three virus strains in one-step growths. Pulse-chase studies of glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…This is relevant because a recent study in CD1d GKO mice concluded that NKT cells (type I and type II) are not critical for protection against the KOS strain of HSV-1 (8), contrasting with our own observations that disease was more severe in CD1d GKO mice infected with the neuropathic strain SC16 than in wt controls (15). Compared to the KOS strain (6,10,11,14,39), a neurovirulent clinical isolate such as SC16 can be expected to exercise the full range of host defenses, and we show here that important differences in the susceptibility of CD1d GKO mice, J␣18 GKO mice, and wt mice to SC16 are dependent on inoculation dose.…”
Section: Discussionmentioning
confidence: 56%
“…This is relevant because a recent study in CD1d GKO mice concluded that NKT cells (type I and type II) are not critical for protection against the KOS strain of HSV-1 (8), contrasting with our own observations that disease was more severe in CD1d GKO mice infected with the neuropathic strain SC16 than in wt controls (15). Compared to the KOS strain (6,10,11,14,39), a neurovirulent clinical isolate such as SC16 can be expected to exercise the full range of host defenses, and we show here that important differences in the susceptibility of CD1d GKO mice, J␣18 GKO mice, and wt mice to SC16 are dependent on inoculation dose.…”
Section: Discussionmentioning
confidence: 56%
“…These studies were facilitated by the observation that the neuroinvasive isolates SP7 (7,21) and 490 (18) share a common tissue culture behavior, the small-plaque phenotype, which includes a restriction in viral glycoprotein processing and virion release, and an ICP34.5 protein with 18 PAT repeats in the center of the protein. In contrast, many attenuated viruses, such as KOS321, SLP5, and SLP10, produce large plaques and have only three PAT repeats (7,18). The ability of the pL/ST plasmid from KOS to genetically transfer the largeplaque phenotype into SP7 and 490 indicated that sequences containing ICP34.5 could eliminate the small-plaque phenotype (7; also data not shown), but the present studies demonstrate that specific isoforms of the ICP34.5 protein confer both the plaque phenotype and neuroinvasive disease potential onto the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from this laboratory identified a tissue culture phenotype which distinguished clinical isolates from the KOS laboratory strain (15). The clinical isolates produce small plaques on Vero cells and are cell associated, and viral glycoprotein processing appears to be restricted to the endoplasmic reticulum (small-plaque phenotype).…”
mentioning
confidence: 99%